MEMBANGUN PERILAKU HIDUP SEHAT DAN BERSIH BAGI SISWA/I PAUD DI LANGSA KOTA MELALUI PENYEDIAAN WASTAFEL PORTABEL CUCI TANGAN - Agus Putra AS; Baihaqi Baihaqi; Abdul Latif (Global Science Society, 2021)
This community service aims to educate early childhood in a healthy and clean lifestyle. The lack of health facilities at the Early Childhood Education/ PAUD level during the COVID-19 pandemic has an impact on the continuity of the teaching and learning process. This program is implemented for 4 months. The target of this program is 4 PAUDs located in Langsa Kota sub-district, namely PAUD Nadya Rabila, PAUD Az-Zikra, PAUD Syakirah and PAUD My Baby School. The main problem faced by the target group is the lack of knowledge in making environmentally friendly portable sinks and the absence of preventive action for children by education providers on early health education for children. The method used in this activity was participatory active discussion and participants through adult learning. Activities carried out include: coordination of activities, provision of tools and materials, assembling a portable sink starting from the stage of determining the design, size and capacity, testing portable sinks, handing over portable sinks to partners and monitoring and evaluating activities with target partners. The results of the activity show that the portable sinks distributed to partners have been used as well as possible in accordance with health protocols and were able to build healthy and clean living habits for PAUD students through the use of portable hand washing sinks.